2017
DOI: 10.1002/phar.1913
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of Long-Acting Beta2-Agonist Combined with a Long-Acting Muscarinic Antagonist or Inhaled Corticosteroid in Chronic Obstructive Pulmonary Disease

Abstract: The LABA/LAMA combination had similar effectiveness to LABA/ICS as measured by exacerbation rates in COPD patients. As a result, characteristics other than effectiveness, such as symptom control, cost, patient preferences, and adverse events, may be important in selecting between the two regimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 29 publications
0
17
1
2
Order By: Relevance
“…Other studies have demonstrated improved efficacy and effectiveness of LABA/LAMA relative to LABA/ICS; this may also result in improvement of extracardiac manifestations and other comorbidities related to COPD, including CCV outcomes. 3,27 -29 Results should be interpreted with caution because the main analysis suggested a marginally decreased risk (about 20%) and the confidence interval approached the null value (0.623-0.997). Additionally, multiple statistical analyses could inflate the likelihood of finding a significant result.…”
Section: Discussionmentioning
confidence: 89%
“…Other studies have demonstrated improved efficacy and effectiveness of LABA/LAMA relative to LABA/ICS; this may also result in improvement of extracardiac manifestations and other comorbidities related to COPD, including CCV outcomes. 3,27 -29 Results should be interpreted with caution because the main analysis suggested a marginally decreased risk (about 20%) and the confidence interval approached the null value (0.623-0.997). Additionally, multiple statistical analyses could inflate the likelihood of finding a significant result.…”
Section: Discussionmentioning
confidence: 89%
“…<…> We based our selection of a 90‐day observation window on existing literature describing heart failure and edema within a few months of pregabalin therapy.” 25 “The primary outcome was hospitalization for COPD or pneumonia within 30 days after the index date <…>” 26 3. Induction period“<…> the effect of insulin on chronic complications may take some time, so we conducted a lag‐time analysis, whereby patients with chronic complication events that occurred 3 years after the initiation of insulin were excluded.” 27 “Outcomes were collected starting 30 days following the index date to ensure that events occurring during the baseline period were not mistakenly captured as study period events.” 28 4. Stockpiling“For overlapping prescriptions, the individual was assumed to have completed the former one before starting the second.” 29 “To account for gaps and overlaps in redemptions due to incomplete adherence or lost prescriptions, we presumed that health‐insured persons have drug stocks lasting up to 15 days due to incomplete compliance (‘15‐ day rule’), added apparent overlaps up to a maximum overlap duration corresponding to 25% of the quantity of the last overlapping prescription, and applied common recommendations to fill apparent gaps between prescriptions using prospective filling.” 30 5.…”
Section: Discussionmentioning
confidence: 99%
“…Die Therapie ist primär inhalativ und erfolgt durch die Applikation von Betamimetika und Anticholinergika über entsprechende Devices. Diese Therapie ist bezüglich der jährlichen Exazerbationsrate und der Lebensqualität wirksam [7]. Als lang wirksame Betamimetika (long-acting beta-2 agonists, LABA) sind Vilanterol, Indacaterol, Olodaterol, Formoterol und Salmeterol, als lang wirksame Anticholinergika (long-acting muscarinic antagonists, LAMA) sind Tiotropium, Glycopyrronium, Aclidnium und Umeclidinium verfügbar.…”
Section: Transfer In Die Praxis Von Dr Helmut Frohnhofen (Witten)unclassified
“…Als lang wirksame Betamimetika (long-acting beta-2 agonists, LABA) sind Vilanterol, Indacaterol, Olodaterol, Formoterol und Salmeterol, als lang wirksame Anticholinergika (long-acting muscarinic antagonists, LAMA) sind Tiotropium, Glycopyrronium, Aclidnium und Umeclidinium verfügbar. Diese Präparate könne als Einzelsubstanzen oder in Kombination verordnet werden, wobei die Kombinationstherapie einen additiven Effekt hat [7]. …”
Section: Transfer In Die Praxis Von Dr Helmut Frohnhofen (Witten)unclassified